2022
DOI: 10.1039/d2tc03463h
|View full text |Cite
|
Sign up to set email alerts
|

Blue heteroleptic iridium(iii) complexes for OLEDs: simultaneous optimization of color purity and efficiency

Abstract: High-performance blue phosphorescent iridium(III) complexes with good efficiency and color purity simultaneously are still the huge challenge. Two blue phosphorescent iridium(III) complexes, (dfdmappy)2Ir(phim) (Ir1) and (dfdmapypy)2Ir(phim) (Ir2) were developed by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…4a and b respectively and the results are summarised in Table 2. Based on theoretical studies (see Theoretical studies section) and comparison with results reported previously for related iridium( iii ) complexes, 15,41,54–57 the intense absorption bands at shorter wavelength (<340 nm) can be assigned to ligand-centred transitions (LC), 15,41,56–59 while the less intense bands at lower energies (>340 nm) are best assigned to admixed ligand centred (LLCT), and metal to ligand charge transfer (MLCT) transitions. 15,41,56,57,59…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…4a and b respectively and the results are summarised in Table 2. Based on theoretical studies (see Theoretical studies section) and comparison with results reported previously for related iridium( iii ) complexes, 15,41,54–57 the intense absorption bands at shorter wavelength (<340 nm) can be assigned to ligand-centred transitions (LC), 15,41,56–59 while the less intense bands at lower energies (>340 nm) are best assigned to admixed ligand centred (LLCT), and metal to ligand charge transfer (MLCT) transitions. 15,41,56,57,59…”
Section: Resultsmentioning
confidence: 81%
“…Based on theoretical studies (see Theoretical studies section) and comparison with results reported previously for related iridium(III) complexes, 15,41,[54][55][56][57] the intense absorption bands at shorter wavelength (<340 nm) can be assigned to ligand-centred transitions (LC), 15,41,[56][57][58][59] while the less intense bands at lower energies (>340 nm) are best assigned to admixed ligand centred (LLCT), and metal to ligand charge transfer (MLCT) transitions. 15,41,56,57,59 The photoluminescence spectra for iridium(III) complexes 12-20 recorded at acidic pH values ( pH = 3.18-3.51) are shown in Fig. 4b and in the case of complex 12 (2-(2-pyridyl)imidazole ancillary ligand) a broad structured emission with a maximum at 519 nm was observed.…”
Section: Photoluminescence Studiesmentioning
confidence: 81%
“…Because of their good color purities, high quantum efficiencies, relatively short phosphorescence lifetimes and high thermal stabilities, iridium(III) complexes are being applied as phosphorescent materials for OLEDs. [1][2][3][4][5][6][7][8][9][10][11] For Ir(III)cyclometalate complexes, the metal-to-ligand charge transfer ( 3 MLCT) involved in the emissive triplet excited state and the rigid octahedral structure can effectively facilitate the radiative decay process and suppress the non-radiative decay route. In addition, the color purities of iridium(III) complexes can be tuned via the addition of various substituents.…”
Section: Introductionmentioning
confidence: 99%